Penerapan Kebijakan Pemerintah dalam Melaksanakan Kegiatan Ketahanan Pangan melalui Badan Usaha Milik Desa (BUMDes) Srikoyo Menongo - Imam Syafi’i; Sofia Tri Septiawati (Perspektif Administrasi Publik dan hukum, 2025)
The Implementation of Government Policy in Conducting Food Security Activities Through the Village-Owned Enterprises (Bumdes) Srikoyo Menongo. Data collection was carried out through interviews with the Director of the Village-Owned Enterprise, the Secretary of the Village-Owned Enterprise, and the Head of Menongo Village, Sukodadi District, Lamongan Regency.